2006
DOI: 10.1158/1078-0432.ccr-06-0459
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Altering Dietary ω-6/ω-3 Fatty Acid Ratios on Prostate Cancer Membrane Composition, Cyclooxygenase-2, and Prostaglandin E2

Abstract: Purpose: To determine whether altering the dietary content of ω-6 (n-6) and ω-3 (n-3) polyunsaturated fatty acids affects the growth of androgen-sensitive prostate cancer xenografts, tumor membrane fatty acid composition, and tumor cyclooxygenase-2 and prostaglandin E2 (PGE2) levels. Experimental Design: Individually caged male severe combined immunodeficiency mice were fed isocaloric 20% kcal fat diets with the fat derived either primarily from n-6 fatty acids (n-6 group) or with the fat consis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
104
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(115 citation statements)
references
References 47 publications
7
104
0
4
Order By: Relevance
“…This inconsistency may be related to the distinct models used and/or differences in experimental design. For instance, Kobayashi and colleagues 38 recently reported that growth of hormone-dependent prostatic LAPC-4 xenograft tumors was inhibited by replacing 50% of dietary fat (corn oil) with fish oil. In contrast to CWR22 tumors, the LAPC-4 cells were shown to express COX-2 and produce PGE 2 , which is a known cell-survival pathway in cancer inhibited by n-3 PUFA, and we examined the affects of dietary PUFA on established tumors rather than their establishment and subsequent growth.…”
Section: Discussionmentioning
confidence: 99%
“…This inconsistency may be related to the distinct models used and/or differences in experimental design. For instance, Kobayashi and colleagues 38 recently reported that growth of hormone-dependent prostatic LAPC-4 xenograft tumors was inhibited by replacing 50% of dietary fat (corn oil) with fish oil. In contrast to CWR22 tumors, the LAPC-4 cells were shown to express COX-2 and produce PGE 2 , which is a known cell-survival pathway in cancer inhibited by n-3 PUFA, and we examined the affects of dietary PUFA on established tumors rather than their establishment and subsequent growth.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, dietary n-6/n-3 fatty acid ratio seems to control not only the membrane fatty acid composition but also the growth of PCa xenografts in preclinical models (Kobayashi et al 2006). Therefore, we may propose that PCa cells over-producing LOX and COX enzymes are able to take an important advantage for their growth from the presence of elevated concentrations of AA in their microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…However, a strict relationship between the amount of available AA in the membrane and the diet exists. In fact, as demonstrated by preclinical studies, intake of dietary n-6 fatty acid regulates the levels of AA not only in serum but also in membrane phospholipids (Kobayashi et al 2006). AA is metabolized via either the cyclooxygenase (COX) or lipoxygenase (LOX) pathway producing prostaglandins and hydroperoxyeicosatetraenoic acids (HETEs) respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Is it just that increased food consumption has resulted in higher BMI, which of itself predisposes the individual to these disorders, or is it truly the type of fat? Mechanistic studies of n-3 and n-6 fats show their role in respectively inhibiting and promoting inflammation and tumour growth (Xia et al 2005;Kobayashi et al 2006), while high levels of n-6 fats may inhibit the action of delta-9 desaturase (Yang et al 1999b), critical for desaturating SFA. So while controlling bodyweight may be the more important strategy, reducing the level of n-6 PUFA to bring down the OMR of the diet appears worthwhile.…”
Section: Components Of Animal Fat With Known Health Benefitsmentioning
confidence: 99%